The epic adventures of Huggie & Stick - Daywalt, Drew (Philomel Books, 2018)
When a grumpy stuffed bunny and a happy-go-lucky stick fall out of their boy's backpack, they embark on an odyssey that takes them all around the world, experiencing one crazy adventure after another.